A rejoinder to J.G.A. Pocock. Issue 3 (3rd April 2019) - James, Samuel
ABSTRACT: I am grateful for J. G. A. Pocock's generous response to my article on his early work and the development of the 'Cambridge School'. In this brief rejoinder, I try to make clear that I meant in no way to diminish the importance of Pocock's achievement, or its centrality to the 'Cambridge School' story, while defending my view of the distinctive character and intellectual genealogy of his work.